The Effect of Individual Characteristics, Competence and Quality of Work Life On Work Motivation, Intention to Leave and Employee Performance Outsoursing Manufacturing Company in East Java Province - Sumantri, Dr.; Brahmasari, Hj.; Mujanah, Hj. (Archives of Business Research, 2017)
The existing regulations are not yet adequate to regulate the outsourcing that has been running in the middle of economic life. This condition affects workers labor/looked at as an object that can be exploited. Outsourcing problems in Indonesia is getting worse along with the practice of outsourcing has been legalised by the Government with the Act No. 13 of 2003 On Labor that much controversy it. This research aims to demonstrate and analyze the influence of individual characteristics, competence, quality of work life against motivation, intention to leave and employee performance employee outsoursing outsourcing manufacturing company in East Java province. The population in the research this is the employee outsourcing manufacturing company in East Java province totaled 774 people and the sample numbered 264 people. Method of data processing is using SEM (Equational Structure Modeling) with AMOS version 18. The result of discussions can be concluded that 1) Characteristics of the individual significant effect on work motivation, 2) Characteristics of the individual significant effect on competency, 3) Characteristics of the individual significant effect on intention to leave, 4) Characteristics of the individual no significant effect on the employee performance, 5) Competence significant effect on work motivation, 6) Competence significant effect on intention to leave, 7) Competence significant effect on to the employee performance, 8) Quality of work life significant effect on work motivation, 9) Quality of work life significant effect on intention to leave, 10) Quality of work life significant effect on the employee performance, 11) Work motivation significant effect on intention to leave, 12) Work Motivation significant effect on the employee performance and 13) Intention to leave no significant effect on the employee performance.